Effect of Isopropyl Alcohol Concentration and Etching Time on Wet Chemical Anisotropic Etching of Low-Resistivity Crystalline Silicon Wafer - Eyad Abdur-Rahman; Ibrahim Alghoraibi; Hassan Alkurdi (International Journal of Analytical Chemistry)
A micropyramid structure was formed on the surface of a monocrystalline silicon wafer (100) using a wet chemical anisotropic etching technique. The main objective was to evaluate the performance of the etchant based on the silicon surface reflectance. Different isopropyl alcohol (IPA) volume concentrations (2, 4, 6, 8, and 10%) and different etching times (10, 20, 30, 40, and 50 min) were selected to study the total reflectance of silicon wafers. The other parameters such as NaOH concentration (12% wt.), the temperature of the solution (81.5°C), and range of stirrer speeds (400 rpm) were kept constant for all processes. The surface morphology of the wafer was analyzed by optical microscopy and atomic force microscopy (AFM). The AFM images confirmed a well-uniform pyramidal structure with various average pyramid sizes ranging from 1 to 1.6 μm. A UV-Vis spectrophotometer with integrating sphere was used to obtain the total reflectivity. The textured silicon wafers show high absorbance in the visible region. The optimum texture-etching parameters were found to be 4–6% vol. IPA and 40 min at which the average total reflectance of the silicon wafer was reduced to 11.22%.